Index Based Spatial Assessment of Heavy Metals in Damsa Dam Lake, Cappadocia/Türkiye - Hüseyin Cüce; Mehmet Ali Dereli; Erkan Kalıpcı (Doğal Afetler ve Çevre Dergisi)
Damsa Dam Lake is significant value to the Cappadocia/Nevşehir region in terms of recreation, fishing and agricultural irrigation. The study was conducted to assess potential harmful elements (PHEs) in the dam and to examine the distribution eco-toxicological effects by Geographical Information System (GIS). Samples were collected for one year at 12 stations on the dam lake according to standard methods. The results of analysis obtained field studies along the spring mix period in the dam showed that high harmful metal(loid)s content (especially, average of 7.38 µg / L As and 4.94 µg/L Cu). According to the average concentration level in surface water, the order of PHEs was determined as follows: Fe > Zn > As > Mn > Al> Cu > Se > Pb >Cr > Hg > Ni > Cd. The findings obtained from the sampling were evaluated according to the relevant water quality regulations. Index-based spatial distribution maps created with ArcGIS showed that heavy metal-polluted lake water layer may have a significant effect on the ecological balance at some stations in the lake. This situation reveals the necessity of ongoing rehabilitation measures in the lake and the importance of sustainable conservation priority management practices.